Thin Film Coplanar Transmission Lines - Dupuis, P.A.J. (My University, 1973)
The theoretical aspects of coplanar waveguides were studied with special emphasis on the attainment of precise characteristic impedances and low losses in the 1-2 Ghz frequency range. To this end, a literature survey was performed, and characteristic impedance design curves were reproduced exactly by means of a digital computer. An exact tolerance analysis method was then performed in order to determine geometrical tolerances which would enable a characteristic impedance of 50 Ω +/- 10% to be attained for a given relative dielectric constant of 9.2 +/- 10%. A loss theory which neglected dielectric losses and assumed thin films of conducting metal less than 1 skin depth thick was also presented. Two similar fabrication techniques were studied and 43 coplanar waveguide samples were fabricated. Of these 43 samples, 32 were tested by swept frequency techniques and time domain reflectometer techniques.
The theory for characteristic impedance was found to be accurate to within +/- 2 Ω providing a few simple design guidelines were followed. The transmission loss theory corresponded very well with experimental measurements, which were estimated to be accurate to within 22%. Furthermore, fixtures for mounting the samples quickly and repetitively were designed and fabricated.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering